33.2k views
2 votes
I need some help with this, it’s from my trigonometry prep guide. It asks to answer (a) and (b) Put these separately so I know which is which ^

I need some help with this, it’s from my trigonometry prep guide. It asks to answer-example-1
User Renetik
by
4.8k points

1 Answer

3 votes

Given the binomial below


(3x^5-(1)/(9)y^3)^4

a) The formula for the summation notation of a binomial theorem is


(a+b)^n=\sum ^n_(r=0)(^n_r)(a)^(n-r)(b)^r

Where


\begin{gathered} a=3x^5 \\ b=-(1)/(9)y^3 \end{gathered}

Substitute for a and b into the formula above


(3x^5-(1)/(9)y^3)^4=\sum ^4_(r=0)(^4_r)(3x^5)^(4-r)(-(1)/(9)y^3)^r

Hence, the answer is


\sum ^4_(r=0)(^4_r)(3x^5)^(4-r)(-(1)/(9)y^3)^r

b) For the simplified terms of the expansion,


\begin{gathered} \sum ^4_(r=0)(^4_r)(3x^5)^(4-r)(-(1)/(9)y^3)^r=(4!)/(0!\left(4-0\right)!)\mleft(3x^5\mright)^4\mleft(-(1)/(9)y^3\mright)^0+(4!)/(1!\left(4-1\right)!)\mleft(3x^5\mright)^3\mleft(-(1)/(9)y^3\mright)^1+(4!)/(2!\left(4-2\right)!)\mleft(3x^5\mright)^2\mleft(-(1)/(9)y^3\mright)^2+(4!)/(3!(4-3)!)(3x^5)^1(-(1)/(9)y^3)^3+(4!)/(4!(4-4)!)(3x^5)^0(-(1)/(9)y^3)^4 \\ =81x^(20)-12x^(15)y^3+(2x^(10)y^6)/(3)-(4x^5y^9)/(243)+(y^(12))/(6561) \end{gathered}

Hence, the answer is


81x^(20)-12x^(15)y^3+(2x^(10)y^6)/(3)-(4x^5y^9)/(243)+(y^(12))/(6561)

User Powlo
by
5.2k points